Preparation method of high-stability photocatalytic titanium sol

CN122875205APending Publication Date: 2026-10-09ANHUI DINO ENVIRONMENTAL NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611144512.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0007]本申请的目的在于提供一种高稳定性光催化钛溶胶的制备方法,用于解决现有钛溶胶的晶相控制依赖高温煅烧处理,容易导致纳米颗粒团聚,影响光催化活性和涂层性能的问题

Benefits of technology

[0033]1、采用过氧化氢与有机酸复配的解胶方式,在40-90℃水浴回流的温和条件下,同步完成偏钛酸的溶胶化分散与晶型的转变,一步生成粒径约10nm的纯锐钛矿相TiO2颗粒,省去后续高温煅烧工序。从而大幅降低生产能耗、并避免颗粒团聚。同时低温液相环境下生成的晶粒具有无硬团聚和单分散性的优点,结晶度与高温煅烧产物相当,从而实现了低能耗的制备与高性能的输出。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875205A_ABST
    Figure CN122875205A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of high-stability photocatalytic titanium sol and relates to the technical field of photocatalytic materials, and comprises the following steps: S1, sulfur removal pretreatment; S11, beating and dispersing; S12, alkali washing for removing sulfur; S13, washing and purifying; S2, gel dissolution and crystallization; S21, preparation of a material liquid; S22, a gel dissolution system; S23, reflux reaction; S3, doping modification; S31, doping source addition; S32, a doping system; S4, pH adjustment and stabilization; S41, pH control; and S42, stabilizer compounding. According to the application, the sol formation and dispersion of metatitanic acid and the transformation of crystal forms are simultaneously completed under the mild conditions of 40-90 DEG C water bath reflux by adopting the gel dissolution mode of hydrogen peroxide and organic acid compounding, and pure anatase TiO2 particles with a particle size of about 10 nm are generated in one step, so that the subsequent high-temperature calcination process is omitted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photocatalytic materials technology, and in particular to a method for preparing a highly stable photocatalytic titanium sol. Background Technology

[0002] Nano-titanium dioxide photocatalysts have broad application prospects in environmental governance fields such as air purification, self-cleaning coatings, and wastewater treatment due to their non-toxicity, good chemical stability, and high photocatalytic activity. Under ultraviolet light irradiation, titanium dioxide can generate hydroxyl radicals and superoxide anion radicals, decomposing organic pollutants such as formaldehyde, benzene, and TVOCs into carbon dioxide and water, while also possessing antibacterial, bactericidal, and surface self-cleaning functions. Existing nano-titanium dioxide photocatalytic materials are mainly prepared using methods such as sol-gel, hydrothermal, and liquid phase deposition. The sol-gel method is widely used due to its simplicity, easy equipment, and suitability for industrial production.

[0003] However, current methods for controlling the crystal phase of titanium sols typically rely on high-temperature calcination, which is not only energy-intensive but also prone to nanoparticle aggregation, affecting photocatalytic activity and coating performance. Existing literature reports that current technologies require calcination at temperatures above 500℃ to obtain anatase TiO2 films. Furthermore, titanium dioxide has a wide band gap, absorbing only ultraviolet light with wavelengths less than 387nm, while ultraviolet light accounts for only 3%–5% of sunlight, limiting its photocatalytic efficiency in practical environments. Moreover, titanium sols suffer from insufficient water stability and storage stability, easily agglomerating and precipitating during room temperature storage, affecting product practicality and industrial application. When industrial metatitanic acid is used as the titanium source, its SO42-... 2- The content of sulfate is generally high. High concentrations of sulfate can form complexes with titanium ions or change the ionic strength of the solution during the desolvation process, easily leading to sol aggregation, gelation, or even failure to form a transparent sol. Currently, there is no systematic literature reporting on the desulfurization process of metatitanic acid for photocatalytic titanium sol.

[0004] In the existing technology, there are also corresponding solutions for the preparation of titanium dioxide sol from metatitanic acid.

[0005] Chinese invention patent CN1769184A discloses a method for preparing highly active titanium dioxide sol using industrial metatitanic acid as raw material. The invention includes the following steps: (1) washing with alkali to remove sulfate ions, (2) adding acid to dissolve the sol, and (3) desolvating the sol in the manner of (a), (b), or (c). When preparing transition metal or rare earth supported (doped) sols, a certain amount of transition metal salt or rare earth salt solution is first prepared and added to the metatitanic acid slurry that has not been washed with alkali, followed by filtration and washing until sulfate ions are removed. When preparing noble metal doped sols, a noble metal salt solution is added to the prepared pure sol, and then the sol is irradiated under ultraviolet light for 0.5-10 hours while continuously stirring. The advantages of this invention are: low raw material price, low pollution, wide availability, good dispersion and crystallinity of the obtained sol, and significantly improved visible light activity through doping technology; further improvements in sol performance are achieved through post-processing technologies such as microwave and ultrasound. The sol particles are very small, belonging to nanomaterials.

[0006] However, although the existing patents mentioned above can prepare doped titanium dioxide sol using industrial metatitanic acid as raw material, their desulfurization process only qualitatively requires washing until sulfate ions are gone. It lacks quantitative standards such as conductivity and sulfate content. It also has limitations such as easy loss of doping source, poor accuracy of doping amount, complex process and lack of nitrogen coverage. The visible light response extension effect is limited. At the same time, the desolvation depends on a single acid sol and special post-processing such as microwave and ultrasound. Summary of the Invention

[0007] The purpose of this application is to provide a method for preparing a highly stable photocatalytic titanium sol, which solves the problem that the crystal phase control of existing titanium sols depends on high-temperature calcination, which easily leads to the aggregation of nanoparticles and affects photocatalytic activity and coating performance.

[0008] This invention provides a highly stable photocatalytic titanium sol, characterized by small particle size, uniform dispersion, good storage stability, and visible light-responsive photocatalytic activity. Furthermore, the method uses industrial metatitanic acid as the titanium source, and directly degelats after desulfurization pretreatment, eliminating the need for high-temperature calcination, simplifying the process, and making it suitable for large-scale production. The invention also provides applications of the photocatalytic titanium sol in air purification, self-cleaning coatings, and water treatment.

[0009] A method for preparing a highly stable photocatalytic titanium sol specifically includes the following steps:

[0010] S1, Desulfurization pretreatment: Designed for industrial metatitanic acid with high sulfur content. If the raw material is high-purity metatitanic acid that has been thoroughly washed with water, the desulfurization process can be omitted and the product can be directly introduced into the degumming process.

[0011] S11, Pulping and Dispersion: The metatitanic acid filter cake and deionized water are mixed in a mixing tank at a mass ratio of 1:3-1:10, and a uniform slurry is formed by stirring with the stirring liquid.

[0012] S12, Alkali washing for desulfurization: Alkali solution is added dropwise through an alkaline solution cylinder and a gel-propelled block while the slurry is being stirred. The alkaline solution is used to adjust the pH value of the slurry to 8.0-11.0. The mixture is stirred and reacted at room temperature to 60°C for 0.5-2 hours to convert the adsorbed metatitanic acid into soluble sulfate.

[0013] S13, Washing and Purification: Collect the filter cake by filtration and centrifugation in the filter centrifuge bucket, and redisperse the filter cake in deionized water in the liquid forming frame for washing until the conductivity of the filtrate is ≤500μS / cm or the content of metatitanic acid is ≤2000ppm.

[0014] S2, Desolution and Crystallization: Simultaneous completion of sol-gelation and crystal transformation, directly generating anatase phase nano-titanium dioxide without the need for subsequent high-temperature calcination;

[0015] S21, Preparation of slurry: Mix the desulfurized metatitanic acid filter cake with deionized water in a mixing tank at a mass ratio of 1:5-1:20, and then disperse it into a uniform slurry by stirring.

[0016] S22, Degumming System: After stirring and dispersing into a uniform slurry, a degumming agent is added through an alkali cylinder and a gel-propelling block. The molar ratio of the degumming agent to TiO2 is 0.1:1-2.0:1. The preferred degumming agent is a combination of hydrogen peroxide and organic acid.

[0017] S23, reflux reaction: under water bath conditions of 40-90℃, the slurry is refluxed and degelatinated for 2-12 hours. The slurry gradually changes from white and turbid to translucent to transparent titanium sol, and pure anatase phase TiO2 particles with a particle size of about 10nm are formed simultaneously.

[0018] S3, Doping Modification: Used to broaden the photoresponse range of titanium dioxide to the visible light region, and can be implemented after desizing;

[0019] S31, Addition of dopant source: Add dopant source solution to titanium sol and stir for 0.5-2 hours to ensure that the dopant element is uniformly incorporated into the titanium dioxide lattice.

[0020] S32, doping system: the doping elements are nitrogen, fluorine, carbon, iron, nickel or silver, and the doping amount is controlled between 0.5-8.0 at%;

[0021] S4, pH adjustment and stabilization: Improve the storage stability of sol through the synergistic effect of pH regulation and stabilizers;

[0022] S41, pH control: Adjust the pH of the titanium sol to a stable range of 2-6 or 8-11 using alkaline or acidic solutions;

[0023] S42, stabilizer compound: Add 0.1%-5% of stabilizer by total mass of titanium sol and stir to mix evenly. The stabilizer is selected from one or more of polyvinylpyrrolidone, polyethylene glycol, polyvinyl alcohol and sodium carboxymethyl cellulose.

[0024] As a further improvement of the present invention, in step S1, the top of the stirring tank is provided with an alkali inlet, a filter cake inlet, and an ionized water inlet. A filter cake funnel is fixedly connected to the top of the filter cake inlet on the top of the stirring tank. A water inlet pipe is fixedly connected through the interior of the ionized water inlet. The metatitanic acid filter cake enters the interior of the stirring tank through the filter cake funnel, and the deionized water enters the interior of the stirring tank through the water inlet pipe. A threaded ring is fixedly connected to the bottom of the stirring tank, and a threaded groove is provided at the top of the inner wall of the liquid forming frame. The threaded ring is threadedly connected to the threaded groove. By setting different functional feed inlets in different zones, the precise and orderly addition of various materials can be achieved. At the same time, the threaded mating structure enables the quick sealing assembly and convenient disassembly of the stirring tank and the liquid forming frame, taking into account both the accuracy of material addition and the convenience of device disassembly and maintenance.

[0025] As a further improvement of the present invention, two bottom baffles are symmetrically fixedly connected inside the bottom end of the mixing tank. A sliding groove is formed on the side of the mixing tank at the center section of the bottom baffle. A push rod is slidably connected inside the sliding groove. A sealing plate is fixedly connected to the push rod near the center of the mixing tank. Both the sealing plate and the bottom baffle are fan-shaped. There are two sealing plates, and a series ring is fixedly connected to one side of the two sealing plates. The sealing plate is slidably connected inside the two bottom baffles. The sealing plate is used to close the space formed by the two bottom baffles. The sliding opening and closing structure of the fan-shaped sealing plate and the bottom baffle, which is linked by the push rod through the series ring, can conveniently control the opening and closing of the space at the bottom of the mixing tank. The process switching between stirring reaction and material discharge separation can be realized without additional valves. The structure is compact and easy to operate.

[0026] As a further improvement of the present invention, the sealing plate is in an open state before stirring. Deionized water is injected into the stirring tank through the water inlet pipe. At this time, the deionized water will enter the liquid-forming frame through the gap formed by the bottom baffle. A transparent observation plate is provided on the side of the liquid-forming frame. The injection is stopped when the deionized water in the liquid-forming frame reaches a suitable amount by observing the transparent observation plate. Then, the sealing plate is controlled by the push rod to close the gap between the bottom baffles. After the gap is closed, metatitanic acid filter cake and deionized water are put into the stirring tank through the water inlet pipe and the filter cake funnel. Before the stirring reaction, the deionized water for washing is pre-stored in the liquid-forming frame, and the water volume is directly and accurately controlled by the transparent observation plate. No additional liquid storage and metering equipment is required. The preparation and reaction processes are seamlessly connected in the same device, simplifying the operation process.

[0027] As a further improvement of the present invention, a series rod is rotatably connected to the top center of the inside of the mixing tank. The mixing liquid is fixedly connected to the outside of the series rod. A protective shell is provided at the bottom of the series rod. A rotary motor is fixedly connected inside the protective shell. The series rod is fixedly connected to the output end of the rotary motor. The mixing of the metatitanic acid filter cake and deionized water into a slurry is carried out by the rotation of the mixing liquid driven by the start of the rotary motor. The rotary motor with an internal protective shell directly drives the mixing liquid to complete the slurry mixing through the series rod. The power transmission is direct and efficient. The protective shell can isolate the slurry and protect the motor. Moreover, the transmission structure is integrated into the tank, and the overall layout is compact and simple.

[0028] As a further improvement of the present invention, the alkali cylinder is fixedly connected to the top of the stirring tank, above the alkali inlet. The alkali is placed inside the alkali cylinder. The outer surface of the alkali cylinder is provided with a transparent observation plate and a scale. The transparent observation plate and the scale are used to quickly observe the amount of alkali stored. The gel-like push block is movably connected to the inside of the alkali cylinder. A pressing rod is fixedly connected to the side of the gel-like push block away from the inside of the alkali cylinder. The gel-like push block and the pressing rod are used to push the alkali in the alkali cylinder from the alkali inlet into the stirring tank. The alkali addition structure at the top of the stirring tank allows for intuitive and precise control of the amount of alkali used with the help of the graduated transparent observation plate. The pressing rod pushes the gel-like block to complete the alkali addition smoothly and controllably. The structure is compact and easy to operate, facilitating precise control of the pH value of the reaction system.

[0029] As a further improvement of the present invention, the centrifugal filter bucket is fixedly connected to the outer surface of the series rod. The centrifugal filter bucket is located between the bottom baffle and the protective shell. During filtration and centrifugal separation, the sliding push rod of the centrifugal filter bucket opens the gap formed by the two bottom baffles, allowing the uniform slurry to be centrifuged and filtered before entering the liquid forming frame. After centrifugation and filtration, the uniform slurry is washed in deionized water pre-prepared in the liquid forming frame. The centrifugal filter bucket and the stirring structure share the rotational power of the series rod, eliminating the need for additional drive. With the opening and closing of the bottom gap, the slurry can be centrifuged and filtered within the same device and directly washed in the pre-stored water in the liquid forming frame, eliminating the material transfer step.

[0030] As a further improvement of the present invention, in step S12, the alkaline washing for desulfurization employs a two-stage gradient alkaline washing process. The first gradient alkaline washing adjusts the slurry pH to 8.5-9.0, and the reaction time at room temperature is 40 minutes. This first gradient alkaline washing is used to dissolve free and weakly adsorbed sulfate ions. The second gradient alkaline washing fine-tunes the pH to 10.0-10.5, and the reaction time is 30 minutes at 50-60°C. This second gradient alkaline washing is used for deep desorption of strongly bound sulfate ions. By progressively increasing the pH and reaction temperature, free, weakly adsorbed, and strongly bound sulfate ions are removed sequentially and in a targeted manner. This achieves deep desulfurization while avoiding excessive damage to the metatitanic acid structure under a single strong alkaline high-temperature condition, resulting in highly targeted and efficient desulfurization.

[0031] As a further improvement of the present invention, in step S13, the washing and purification adopts a staged countercurrent washing process, wherein the filtrate from the final washing with clean water is used as the pulping water for the previous washing stage. Reusing the filtrate from the final washing with clean water as pulping water for the previous washing stage can effectively improve water resource utilization and reduce fresh water consumption and wastewater discharge while ensuring the washing and purification effect.

[0032] Compared with the prior art, the beneficial effects of this invention are as follows:

[0033] 1. A degellation method using a combination of hydrogen peroxide and organic acids is employed. Under mild conditions of reflux in a water bath at 40-90℃, the sol-gel dispersion and crystal transformation of metatitanic acid are simultaneously completed, generating pure anatase TiO2 particles with a particle size of approximately 10nm in one step, eliminating the need for subsequent high-temperature calcination. This significantly reduces production energy consumption and avoids particle agglomeration. Furthermore, the crystals generated in the low-temperature liquid phase environment have the advantages of being free from hard agglomeration and monodisperse, with crystallinity comparable to that of the high-temperature calcined products, thus achieving low-energy preparation and high-performance output.

[0034] 2. By employing a two-stage gradient alkali washing process, the problem of easy agglomeration and gelation during the desolvation of high-sulfur metatitanic acid is fundamentally solved. At the same time, gradient alkali washing avoids the damage to the microstructure of metatitanic acid caused by excessive alkali treatment. The purified metatitanic acid crystallizes faster and has a more uniform grain size in the subsequent desolvation stage. The desulfurization pretreatment not only achieves the purification of raw materials but also indirectly improves the crystallization quality and dispersion stability of the final sol.

[0035] 3. Adding doping elements in the later stage of the degellation reaction and the grain growth stage, and continuously refluxing to uniformly incorporate elements such as nitrogen, fluorine, carbon, and iron into the titanium dioxide lattice, directly broadens the light response range of titanium dioxide to the visible light region, and significantly improves the visible light catalytic degradation efficiency.

[0036] 4. Employing electrostatic stabilization and steric hindrance, the pH of the sol is first precisely adjusted to the electrostatically stable range, thereby enhancing the electrostatic repulsion between particles. Then, polyvinylpyrrolidone and polyethylene glycol, high-molecular-weight stabilizers, are added to form a steric barrier. This ensures that the sol does not exhibit significant precipitation when stored at room temperature in a sealed container. Simultaneously, the addition of stabilizers does not impair the optical and surface application properties of the coating. After coating, the transmittance in the visible light region is close to that of blank glass, and it also possesses excellent self-cleaning properties.

[0037] 5. All preparation processes, including pulping and dispersion, alkali washing and desulfurization, centrifugal washing and purification, degelatinization and crystallization, doping modification, and pH adjustment and stabilization, are completed within a device assembled from a mixing tank and a liquid-forming frame. This eliminates the need to transfer materials between multiple devices, reducing material losses and the risk of introducing external impurities during material transfer. Simultaneously, the device reuses the power for stirring and centrifugal filtration, significantly improving the reproducibility of the process after scale-up and providing a simple and reliable solution for large-scale stable production. Attached Figure Description

[0038] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0039] Figure 1 This is a flowchart of the steps of the present invention.

[0040] Figure 2 This is a three-dimensional structural diagram of the present invention.

[0041] Figure 3 This is a three-dimensional structural diagram of the liquid-forming frame in this invention.

[0042] Figure 4 This is a three-dimensional structural diagram of the alkali cylinder and the gel-like pushing block in this invention.

[0043] Figure 5 This is a three-dimensional structural diagram of the mixing tank and bottom baffle in this invention.

[0044] Figure 6 This is a three-dimensional structural diagram of the alkali inlet, filter cake inlet, and deionized water inlet in this invention.

[0045] Figure 7 This is a cross-sectional three-dimensional structural diagram of the mixing tank in this invention.

[0046] Figure 8 This is a three-dimensional structural diagram of the series rod and stirring liquid in this invention.

[0047] Figure 9 For the present invention Figure 8 A magnified three-dimensional structural diagram at point A in the middle.

[0048] In the diagram: 101. Stirring tank; 102. Water inlet pipe; 103. Filter cake funnel; 104. Alkali solution cylinder; 105. Transparent observation plate one; 106. Scale; 107. Colloidal pusher block; 108. Pressing rod; 109. Threaded ring; 110. Bottom baffle; 111. Sliding groove; 112. Alkali solution outlet; 113. Filter cake inlet; 114. Deionized water inlet; 201. Liquid forming frame; 202. Transparent observation plate two; 203. Threaded groove; 301. Protective shell; 302. Rotary motor; 303. Connecting rod; 304. Stirring liquid; 305. Filter centrifuge bucket; 306. Connecting ring; 307. Sealing plate; 308. Pusher rod. Detailed Implementation

[0049] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0050] Example 1 illustrates a method for preparing a highly stable photocatalytic titanium sol using high-purity metatitanic acid directly by desolvation. In this example, fully washed high-purity metatitanic acid is used as raw material, directly omitting the desulfurization pretreatment step. The desolvation, crystallization, and stabilization treatments are completed by a reaction device consisting of a stirring tank 101 and a liquid-forming frame 201.

[0051] Raw materials: Metatitanic acid filter cake that has been thoroughly washed and bleached with water, with a TiO2 mass fraction of 35%, Fe content of 32 ppm, and SO4 content of 35%. 2- The content is 1780ppm, and the conductivity of the filtrate is 285μS / cm, which meets the purity requirements for direct gel decomposition.

[0052] Device assembly: Align the threaded ring 109 at the bottom of the mixing tank 101 with the threaded groove 203 at the top of the inner wall of the liquid forming frame 201, and tighten to complete the sealing connection of the upper and lower cavities; push the push rod 308 in the sliding groove 111 to drive the two sealing plates 307 connected by the series ring 306 to slide to the empty position of the bottom baffle 110, and completely seal the bottom of the mixing tank 101.

[0053] like Figure 1 As shown, it includes the following steps:

[0054] S2, Degelatination and Crystallization: Simultaneous completion of sol-gelation and crystal transformation, directly generating anatase phase nano-titanium dioxide without the need for subsequent high-temperature calcination.

[0055] S21, Preparation of the slurry: The metatitanic acid filter cake is fed into the mixing tank 101 through the filter cake funnel 103 and filter cake inlet 113, with a TiO2 content of 8.0 g. Deionized water is injected into the mixing tank 101 through the water inlet pipe 102 and deionized water inlet 114, controlling the mass ratio of filter cake to deionized water to be 1:12.5, with a total addition of 100 mL of deionized water. The rotary motor 302 inside the protective shell 301 is started, driving the series rod 303 to rotate, causing the stirring liquid 304 fixed outside the series rod 303 to continuously stir and disperse into a uniform slurry.

[0056] S22, Desiccation system: Keep the stirring liquid 304 in a stirring state, add desiccation agent to the stirring tank 101. The desiccation agent is a combination of hydrogen peroxide and citric acid, of which 15 mL of 30% hydrogen peroxide solution and 0.6 g of citric acid are added, and the molar ratio of desiccation agent to TiO2 is controlled to be about 0.8:1.

[0057] S23, reflux reaction: The entire device is placed in a water bath environment, and the water bath temperature is controlled at 80℃. Reflux and degelatinize for 6 hours. During the reaction, the stirring liquid 304 is kept at a low speed. The slurry gradually changes from white and turbid to translucent to transparent light yellow titanium sol, and pure anatase phase TiO2 particles with a particle size of about 10nm are formed simultaneously, without the need for subsequent high-temperature calcination.

[0058] S4, pH adjustment and stabilization: Improve the storage stability of sol through the synergistic effect of pH regulation and stabilizers.

[0059] S41, pH Adjustment: After the sol cools to room temperature, add 0.1 mol / L ammonia water dropwise to the stirring tank 101 to adjust the pH value of the titanium sol to a stable range of 4.0. S42, Stabilizer Preparation: Add 1.2% (by mass) of polyvinylpyrrolidone to the titanium sol, and stir the mixture at 30°C for 30 minutes until homogeneous, completing the preparation of the highly stable photocatalytic titanium sol.

[0060] Performance characterization:

[0061] XRD analysis: The diffraction peaks indicate a pure anatase phase with good crystallinity and a grain size of approximately 9.96 nm.

[0062] Zeta potential: -41.2mV, pH=4.0, absolute value greater than 35mV, good stability.

[0063] Photocatalytic performance: Under visible light, the degradation rate of formaldehyde is 86.3% after 8 hours, and the degradation rate of methylene blue is 94.8% after 2 hours.

[0064] Stability test: After 6 months of sealed storage at room temperature, the sol remained pale yellow and translucent, with no precipitation. The absolute value of the Zeta potential remained at 35.8 mV, and the photocatalytic activity remained at 93.5% of the initial activity.

[0065] Example 2 illustrates a method for preparing a highly stable photocatalytic titanium sol, using industrial high-sulfur metatitanic acid after desulfurization as an example. This example is designed for industrial metatitanic acid with high sulfur content, employing a two-stage gradient alkali washing and graded countercurrent washing process to complete the desulfurization pretreatment, followed by degelatination, crystallization, and stabilization to prepare the titanium sol, fully covering all the device components and process steps of the claims.

[0066] Raw material: Unwashed metatitanic acid filter cake from a sulfuric acid process titanium dioxide plant, with a TiO2 mass fraction of 28%, Fe content of 85 ppm, and initial SO4 content of 100%. 2- The content is 6200 ppm on a dried basis, and the conductivity of the filtrate is 8500 μS / cm.

[0067] Device assembly: Screw the threaded ring 109 at the bottom of the mixing tank 101 into the threaded groove 203 at the top of the inner wall of the liquid forming frame 201 to complete the sealing assembly of the upper and lower cavities; In the initial state, the push rod 308 is located outside the sliding groove 111, and the two sealing plates 307 connected by the series ring 306 are retracted into the bottom baffle 110, and the bottom space of the mixing tank 101 is in the open state.

[0068] like Figure 1 As shown, it includes the following steps:

[0069] S1, Desulfurization Pretreatment: Desulfurization pretreatment is designed for industrial metatitanic acid with high sulfur content. If the raw material is high-purity metatitanic acid that has been thoroughly washed with water, desulfurization can be omitted and the product can directly proceed to the degumming process.

[0070] S11, Pulping and Dispersion: First, deionized water is injected into the mixing tank 101 through the water inlet pipe 102 and the deionized water inlet 114. The water flows into the liquid-forming frame 201 through the gap formed by the bottom baffle 110. The liquid level is observed through the transparent observation plate 202 on the side of the liquid-forming frame 201. When the deionized water in the liquid-forming frame 201 accumulates to 150mL, the injection is stopped. Then, the push rod 308 in the sliding groove 111 is pushed, which drives the sealing plate 307 to slide along the bottom baffle 110, completely sealing the bottom gap. A metatitanic acid filter cake with a TiO2 content of 16.0g is weighed and added to the mixing tank 101 through the filter cake funnel 103 and the filter cake inlet 113. Deionized water is then added again through the water inlet pipe 102 to a total volume of 200mL, controlling the mass ratio of filter cake to deionized water to be 1:7. Start the rotary motor 302 inside the protective shell 301, and drive the stirring liquid 304 to stir at a constant speed for 30 minutes through the connecting rod 303 to form a uniform slurry.

[0071] S12, Alkali washing for desulfurization: A two-stage gradient alkali washing process is adopted. The alkali solution is stored inside the alkali solution cylinder 104. The alkali solution cylinder 104 is fixed above the alkali solution port 112 at the top of the stirring tank 101. The cylinder body is equipped with a transparent observation plate 105 and a scale 106, which can monitor the remaining amount of alkali solution in real time.

[0072] First-gradient alkaline washing: Keep the stirring liquid 304 in a stirring state, press the pressing rod 108 at the top of the alkaline liquid cylinder 104, push the colloidal pushing block 107 down along the inner wall of the alkaline liquid cylinder 104, and slowly drip 10% ammonia water by mass into the slurry through the alkaline liquid port 112, and adjust the pH value of the slurry to 8.5-9.0; stir and react at room temperature for 40 minutes to dissolve free and weakly adsorbed sulfate ions, converting them into soluble sulfates.

[0073] Second-gradient alkaline washing: Continue to add alkaline solution by pressing rod 108 and colloid push block 107 to finely adjust the pH value of the slurry to 10.0-10.5; raise the water bath to 55℃ and continue stirring and reacting for 30 minutes to deeply desorb strongly bound sulfate ions.

[0074] S13, Washing and Purification: A staged countercurrent washing process is adopted. After the alkaline washing reaction is completed, the push rod 308 is pulled outward, causing the sealing plate 307 to slide outward along the bottom baffle 110, opening the bottom cavity of the stirring tank 101. The rotary motor 302 is kept running, and the series rod 303 drives the filter centrifuge 305 to rotate synchronously. The slurry is filtered and separated by centrifugal force through the filter centrifuge 305. The filter cake is retained in the filter centrifuge 305, and the filtrate containing sulfate flows into the liquid collection frame 201 and mixes with the pre-stored deionized water. After the first centrifugal filtration is completed, the bottom cavity is closed, and deionized water is re-injected into the stirring tank 101 for pulping and washing. The cavity is then opened again for centrifugal filtration to collect the filter cake. The filtrate from the last wash is used as the pulping water for the previous stage of washing. The washing is repeated 3 times until the conductivity of the last filtrate is ≤215μS / cm and the SO4 content in the filter cake is reduced. 2- The content was reduced to 86 ppm, and the desulfurization rate reached 98.6%.

[0075] S2, Desolution and Crystallization: Desolution and crystallization simultaneously complete sol-gelation and crystal transformation, directly generating anatase phase nano-titanium dioxide without the need for subsequent high-temperature calcination.

[0076] S21, Preparation of the slurry: The desulfurized metatitanic acid filter cake is redispersed in the mixing tank 101, 120mL of deionized water is added, and the mass ratio of filter cake to deionized water is controlled to be about 1:7.5. The mixture is then stirred and dispersed into a uniform slurry by the stirring liquid 304.

[0077] S22, Degelling system: Add degelling agent while stirring. The degelling agent is a combination of hydrogen peroxide and citric acid. Add 18 mL of 30% hydrogen peroxide solution and 0.8 g of citric acid. The molar ratio of degelling agent to TiO2 is approximately 0.75:1.

[0078] S23, reflux reaction: control the water bath temperature at 80℃ and reflux for 6 hours to degelatinate; the slurry gradually changes from white turbidity to translucent light yellow titanium sol, and pure anatase phase TiO2 particles with a particle size of about 10nm are generated simultaneously.

[0079] S4, pH Adjustment and Stabilization: pH Adjustment and Stabilization: Improve the storage stability of sols through the synergistic effect of pH regulation and stabilizers.

[0080] S41, pH adjustment: After the sol is cooled to room temperature, dilute ammonia is added dropwise through the alkali container 104 to adjust the pH value of the titanium sol to 4.2.

[0081] S42, stabilizer compound: Add 1.0% polyvinylpyrrolidone by the total mass of titanium sol, stir for 30 minutes until uniformly mixed, and obtain the final photocatalytic titanium sol.

[0082] Performance characterization:

[0083] XRD analysis: The diffraction peaks indicate a pure anatase phase with good crystallinity and a grain size of approximately 10.06 nm.

[0084] Zeta potential: -39.8mV, pH=4.2.

[0085] Photocatalytic performance: The formaldehyde degradation rate was 85.9% after 8 hours under visible light, which is comparable to the performance in Example 1.

[0086] Storage stability: After being sealed at room temperature for 6 months, the sol remained translucent with no precipitation, the absolute value of the Zeta potential was 34.2 mV, and the activity remained at 92% of the initial value.

[0087]

[0088] Example 3, taking nitrogen-doped modified high-stability photocatalytic titanium sol as an example, describes a method for preparing high-stability photocatalytic titanium sol. In this example, based on the industrial desulfurization pretreatment of metatitanic acid, nitrogen doping modification is introduced to broaden the photoresponse range to the visible light region. The entire preparation process is completed using an assembly device consisting of a stirring tank 101 and a liquid-forming frame 201.

[0089] Raw materials: High-sulfur metatitanic acid filter cake as in Example 2, initial SO4 2- Content 6200ppm.

[0090] like Figure 1 As shown, it includes the following steps:

[0091] S1, Desulfurization Pretreatment: The procedure was carried out exactly as described in S1 of Example 2. The filter cake was obtained after two-stage gradient alkaline washing and graded countercurrent washing to remove sulfur and purify the metatitanic acid.

[0092] S2, Desolution and Crystallization: Desolution and crystallization simultaneously complete sol-gelation and crystal transformation, directly generating anatase phase nano-titanium dioxide without the need for subsequent high-temperature calcination.

[0093] S21, Preparation of the slurry: Take a filter cake with a TiO2 content of 8.0g after desulfurization and put it into the mixing tank 101. Add 100mL of deionized water and stir and disperse it into a uniform slurry through the stirring liquid 304.

[0094] S22, Degelatinization system: Add 15 mL of 30% hydrogen peroxide solution and 0.5 g of citric acid as degelatinizing agent. The molar ratio of degelatinizing agent to TiO2 is approximately 0.7:1.

[0095] S23, reflux reaction: control the water bath temperature at 80℃, reflux and degelatinate for 4 hours, and the slurry will initially transform into a semi-transparent sol state.

[0096] S3, doping modification: used to broaden the light response range of titanium dioxide to the visible light region, and can be implemented after desizing.

[0097] S31, Adding dopant source: Add urea solution as nitrogen dopant source to the titanium sol in the stirring tank 101, keep the stirring liquid 304 continuously stirred, and react for 1 hour to make the dopant element uniformly incorporated into the titanium dioxide lattice.

[0098] S32, doping system: nitrogen was selected as the doping element, and the doping amount was controlled at 3.0 at; after doping, the reflux was continued for 2 hours to obtain a light yellow transparent nitrogen-doped titanium sol.

[0099] S4, pH adjustment and stabilization: Improve the storage stability of sol through the synergistic effect of pH regulation and stabilizers.

[0100] S41, pH adjustment: After the sol cools to room temperature, adjust the pH value to 4.0 with dilute ammonia.

[0101] S42, stabilizer compound: Add 1.0% polyvinylpyrrolidone by the total mass of the sol, stir for 30 minutes to mix evenly, and obtain nitrogen-doped photocatalytic titanium sol.

[0102] Performance characterization: The formaldehyde degradation rate was 93.2% after 8 hours under visible light and reached 98.4% after 12 hours, indicating a significant improvement in visible light photocatalytic activity.

[0103] Example 4 illustrates a method for preparing a highly stable photocatalytic titanium sol using iron-doped modified titanium sol as an example. In this example, iron is used for doping modification to adapt to a weakly acidic stable range and a polyethylene glycol stabilizer system.

[0104] like Figure 1 As shown, it includes the following steps:

[0105] The raw materials and S1 are the same as in Example 2.

[0106] S2, Degelatination and Crystallization: Simultaneous completion of sol-gelation and crystal transformation, directly generating anatase phase nano-titanium dioxide without the need for subsequent high-temperature calcination.

[0107] S21, Preparation of the slurry: Take a filter cake containing 8.0g of TiO2 after desulfurization and put it into the mixing tank 101. Add 100mL of deionized water and stir and disperse it into a uniform slurry through the stirring liquid 304.

[0108] S22, Degelatinization system: Add 15 mL of 30% hydrogen peroxide solution and 0.3 g of tartaric acid as degelatinizing agent. The molar ratio of degelatinizing agent to TiO2 is approximately 0.65:1.

[0109] S23, reflux reaction: control the water bath temperature at 85℃, reflux for 4 hours to degelatinate.

[0110] S3, doping modification: used to broaden the light response range of titanium dioxide to the visible light region, and can be implemented after desizing.

[0111] S31, Addition of dopant source: Add 5 mL of 0.1 mol / L ferric nitrate solution to the titanium sol as an iron dopant source, and keep the stirring liquid at 304 for 1 hour to make the iron element uniformly dispersed and incorporated into the titanium dioxide lattice.

[0112] S32, doping system: the doping element is iron, Fe 3+ The doping amount was approximately 2.0 at; after doping, the gel was further defused by refluxing for 2 hours to obtain a pale yellow iron-doped titanium sol.

[0113] S4, pH adjustment and stabilization: Improve the storage stability of sol through the synergistic effect of pH regulation and stabilizers.

[0114] S41, pH adjustment: After the sol cools to room temperature, adjust the pH value to 6.0 with dilute nitric acid.

[0115] S42, stabilizer compound: Add 0.8% polyethylene glycol PEG-4000 by the total mass of the sol, stir for 30 minutes to mix evenly, and obtain iron-doped photocatalytic titanium sol.

[0116] Performance characterization: The formaldehyde degradation rate is 90.8% after 8 hours under visible light, exhibiting both visible light response and good storage stability.

[0117] Comparative Example 1: No desulfurization treatment. The same batch of high-sulfur metatitanic acid from Example 2 was used, and without desulfurization pretreatment, it was directly degellated under the degelation conditions of Example 2. Results: After 1 hour of degelation, the slurry gradually thickened, and after 3 hours, a white gel formed, making it impossible to obtain a sol. This indicates that the high concentration of sulfate ions severely hindered the degelation process, making it impossible to obtain a stable titanium sol.

[0118] Comparative Example 2: Commercially available P25 powder dispersion. Commercially available P25TiO2 nanoparticles were ultrasonically dispersed in deionized water at a concentration of 5 wt% to prepare a P25 dispersion as a control.

[0119] Photocatalytic performance test

[0120] Test Method 1: Formaldehyde Degradation Test. The P25 dispersions from Examples 1, 2, 3, 4, and Comparative Example 2 were sprayed onto the surface of a 10cm × 10cm glass plate and dried at room temperature to form a film. The coated glass plate was placed in a 1m³ sealed test chamber, and formaldehyde gas was injected into the chamber to achieve an initial concentration of 1.0 mg / m³. Three 15W ordinary fluorescent lamps (approximately 2000 lx) were used as the light source and continuously irradiated the test chamber. The formaldehyde concentration in the chamber was sampled and measured at regular intervals.

[0121] Test results:

[0122]

[0123] Test results show that the titanium sol prepared in the embodiments of the present invention exhibits excellent photocatalytic degradation performance for formaldehyde. The nitrogen-doped titanium sol in Example 3 achieved a formaldehyde degradation rate of 93.2% after 8 hours of light irradiation and 98.4% after 12 hours, significantly better than commercially available P25 dispersion. The excellent performance of Examples 1 and 2 (metatialic acid route) verifies the feasibility of the metatialic acid route.

[0124] Test Method 2: Methylene Blue Degradation Test. Take 20 mL of the titanium sol prepared in Example 1, dilute it to 100 mL, add methylene blue to make its concentration 10 mg / L, stir in the dark for 30 minutes to reach adsorption equilibrium, and then irradiate with a UV lamp. Take a sample every 30 minutes to measure the absorbance of the solution at 664 nm.

[0125] Test results:

[0126]

[0127] Test results show that the titanium sol of the present invention has excellent photocatalytic degradation performance of methylene blue under ultraviolet light irradiation, with a degradation rate of over 94% after 120 minutes, which is significantly better than that of P25 powder dispersion.

[0128] Storage stability test: The titanium sols prepared in Examples 1, 2 and 3 were sealed and stored at room temperature. Samples were taken periodically to observe the precipitation and to test the zeta potential and photocatalytic activity.

[0129] Test results:

[0130]

[0131] Test results show that the titanium sol prepared by this invention has excellent storage stability. In Example 3, after 12 months of storage at room temperature, the absolute value of the Zeta potential remained above 36 mV, and the photocatalytic activity remained above 91% of the initial activity.

[0132] Coating performance testing: transmittance test. The titanium sol prepared in Example 1 was coated onto the surface of a glass slide by dip coating and dried at room temperature. The transmittance of the coating in the wavelength range of 400~700nm was measured using a UV-Vis spectrophotometer.

[0133] Test results: The transmittance of the coating in the wavelength range of 400~700nm is only about 4~5 percentage points lower than that of the blank glass. The transmittance at 400nm is 85.3% and the transmittance at 550nm is 89.7%, which shows good light transmittance and is suitable for surface coating of transparent substrates such as glass and transparent plastics.

[0134] Water contact angle test: The water contact angle of the titanium sol coating surface was tested using a contact angle meter.

[0135] Test results: The water contact angle of the coating was 42° under no light conditions. After 2 hours of UV irradiation, the water contact angle decreased to below 7°, demonstrating excellent superhydrophilicity and self-cleaning properties.

[0136] Finally, it should be noted that the above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a highly stable photocatalytic titanium sol, characterized in that, Specifically, the steps include the following: S1, Desulfurization pretreatment: Designed for industrial metatitanic acid with high sulfur content. If the raw material is high-purity metatitanic acid that has been thoroughly washed with water, the desulfurization process can be omitted and the product can be directly introduced into the degumming process. S11, Pulping and Dispersion: The metatitanic acid filter cake and deionized water are mixed in a mixing tank (101) at a mass ratio of 1:3-1:10, and stirred by stirring liquid (304) to form a uniform slurry; S12, Alkali washing to remove sulfur: Alkali solution is added dropwise through the alkali solution cylinder (104) and the colloidal push block (107) under the stirring state of the stirring liquid (304). The alkali solution is used to adjust the pH value of the slurry to 8.0-11.

0. The reaction is stirred for 0.5-2 hours under the conditions of room temperature to 60°C to convert the adsorbed metatitanic acid into soluble sulfate. S13, Washing and Purification: Collect the filter cake by filtration and centrifugation in the filter centrifuge (305), and redisperse the filter cake in deionized water in the liquid-forming frame (201) until the conductivity of the filtrate is ≤500μS / cm or the content of metatitanic acid is ≤2000ppm. S2, Desolution and Crystallization: Simultaneous completion of sol-gelation and crystal transformation, directly generating anatase phase nano-titanium dioxide without the need for subsequent high-temperature calcination; S21, Preparation of liquid: The desulfurized metatitanic acid filter cake and deionized water are mixed in a mixing tank (101) at a mass ratio of 1:5-1:20, and then dispersed into a uniform slurry by stirring with a stirring liquid (304). S22, Desiccant system: After stirring and dispersing into a uniform slurry, a desiccant is added through an alkali cylinder (104) and a gel-propelling block (107). The molar ratio of the desiccant to TiO2 is 0.1:1-2.0:

1. The desiccant is preferably a combination of hydrogen peroxide and organic acid. S23, reflux reaction: under water bath conditions of 40-90℃, the slurry is refluxed and degelatinated for 2-12 hours. The slurry gradually changes from white and turbid to translucent to transparent titanium sol, and pure anatase phase TiO2 particles with a particle size of about 10nm are formed simultaneously. S3, Doping Modification: Used to broaden the photoresponse range of titanium dioxide to the visible light region, and can be implemented after desizing; S31, Addition of dopant source: Add dopant source solution to titanium sol and stir for 0.5-2 hours to ensure that the dopant element is uniformly incorporated into the titanium dioxide lattice. S32, doping system: the doping elements are nitrogen, fluorine, carbon, iron, nickel or silver, and the doping amount is controlled between 0.5-8.0 at%; S4, pH adjustment and stabilization: Improve the storage stability of sol through the synergistic effect of pH regulation and stabilizers; S41, pH control: Adjust the pH of the titanium sol to a stable range of 2-6 or 8-11 using alkaline or acidic solutions; S42, stabilizer compound: Add 0.1%-5% of stabilizer by total mass of titanium sol and stir to mix evenly. The stabilizer is selected from one or more of polyvinylpyrrolidone, polyethylene glycol, polyvinyl alcohol and sodium carboxymethyl cellulose.

2. The method for preparing a highly stable photocatalytic titanium sol as described in claim 1, characterized in that: In step S1, the top of the stirring tank (101) is provided with an alkali inlet (112), a filter cake inlet (113) and an ionized water inlet (114). A filter cake funnel (103) is fixedly connected above the stirring tank (101) at the top of the filter cake inlet (113). A water inlet pipe (102) is fixedly connected through the interior of the ionized water inlet (114). The metatitanic acid filter cake enters the interior of the stirring tank (101) through the filter cake funnel (103). The deionized water enters the interior of the stirring tank (101) through the water inlet pipe (102). A threaded ring (109) is fixedly connected to the bottom of the stirring tank (101). A threaded groove (203) is provided at the top of the inner wall of the liquid forming frame (201). The threaded ring (109) is threadedly connected to the threaded groove (203).

3. The method for preparing a highly stable photocatalytic titanium sol as described in claim 2, characterized in that: Two bottom baffles (110) are symmetrically fixedly connected inside the bottom end of the mixing tank (101). A sliding groove (111) is provided on the side of the mixing tank (101) at the center section of the bottom baffle (110). A push rod (308) is slidably connected inside the sliding groove (111). A sealing plate (307) is fixedly connected to the push rod (308) near the center of the mixing tank (101). Both the sealing plate (307) and the bottom baffle (110) are fan-shaped. There are two sealing plates (307). A series ring (306) is fixedly connected to the two sealing plates (307) close to each other on one side. The sealing plate (307) is slidably connected inside the two bottom baffles (110). The sealing plate (307) is used to close the space formed by the two bottom baffles (110).

4. The method for preparing a highly stable photocatalytic titanium sol as described in claim 3, characterized in that: Before stirring, the sealing plate (307) of the stirring liquid (304) is in an open state. Deionized water is injected into the stirring tank (101) through the water inlet pipe (102). At this time, the deionized water will enter the liquid forming frame (201) through the gap formed by the bottom baffle (110). A transparent observation plate (202) is provided on the side of the liquid forming frame (201). When the deionized water in the liquid forming frame (201) accumulates to a suitable amount by observing the transparent observation plate (202), the injection is stopped. Then, the sealing plate (307) is controlled by the push rod (308) to close the gap between the bottom baffle (110). After the gap is closed, metatitanic acid filter cake and deionized water are put into the stirring tank (101) through the water inlet pipe (102) and the filter cake funnel (103).

5. The method for preparing a highly stable photocatalytic titanium sol as described in claim 4, characterized in that: A series rod (303) is rotatably connected to the top center of the inside of the mixing tank (101). The mixing liquid (304) is fixedly connected to the outside of the series rod (303). A protective shell (301) is provided at the bottom of the series rod (303). A rotary motor (302) is fixedly connected inside the protective shell (301). The series rod (303) is fixedly connected to the output end of the rotary motor (302). The mixing of the metatitanic acid filter cake and deionized water into a slurry is carried out by the rotation of the mixing liquid (304) driven by the start of the rotary motor (302).

6. The method for preparing a highly stable photocatalytic titanium sol as described in claim 2, characterized in that: The alkali cylinder (104) is fixedly connected to the top of the stirring tank (101) above the alkali inlet (112). The alkali is placed inside the alkali cylinder (104). The outer surface of the alkali cylinder (104) is provided with a transparent observation plate (105) and a scale (106). The transparent observation plate (105) and the scale (106) are used to quickly observe the storage amount of alkali. The gelatinous push block (107) is movably connected to the inside of the alkali cylinder (104). A pressing rod (108) is fixedly connected to the side of the gelatinous push block (107) away from the inside of the alkali cylinder (104). The gelatinous push block (107) and the pressing rod (108) are used to push the alkali in the alkali cylinder (104) from the alkali inlet (112) into the stirring tank (101).

7. The method for preparing a highly stable photocatalytic titanium sol as described in claim 5, characterized in that: The centrifugal filter bucket (305) is fixedly connected to the outer surface of the series rod (303). The centrifugal filter bucket (305) is located between the bottom baffle (110) and the protective shell (301). When the centrifugal filter bucket (305) filters and centrifuges, the sliding push rod (308) opens the space formed by the two bottom baffles (110). The uniform slurry is centrifuged and filtered through the centrifugal filter bucket (305) and then enters the liquid forming frame (201). After centrifugation and filtration, the uniform slurry will be washed in the deionized water prepared in advance in the liquid forming frame (201).

8. The method for preparing a highly stable photocatalytic titanium sol as described in claim 1, characterized in that: In step S12, the alkaline washing for desulfurization employs a two-stage gradient alkaline washing process. The first gradient alkaline washing adjusts the pH of the slurry to 8.5-9.0, and the reaction time at room temperature is 40 minutes. This first gradient alkaline washing is used to dissolve free and weakly adsorbed sulfate ions. The second gradient alkaline washing finely adjusts the pH to 10.0-10.5, and the reaction time is 30 minutes at room temperature (50-60°C). This second gradient alkaline washing is used to deeply desorb strongly bound sulfate ions.

9. The method for preparing a highly stable photocatalytic titanium sol as described in claim 1, characterized in that: In step S13, the washing and purification process adopts a staged countercurrent washing process, wherein the filtrate from the final washing with clean water is used as the pulping water for the previous washing stage.

Citation Information

Patent Citations

  • Method for preparing high activity titanium dioxide sol using industrial metatitanic acid as material

    CN1769184A